2014
DOI: 10.3171/2014.7.focus14160
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgery for cerebral arteriovenous malformations: postoperative outcomes and predictors of complications in 264 cases

Abstract: Object The authors conducted a study to assess the safety and efficacy of microsurgical resection of arteriovenous malformations (AVMs) and determine predictors of complications. Methods A total of 264 patients with cerebral AVMs were treated with microsurgical resection between 1994 and 2010 at the Jefferson Hospital for Neuroscience. A review of patient data was performed, including initial hemorrhage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
3
18
0
2
Order By: Relevance
“…[45] Theofanis et al reported 264 patients treated with microsurgery and showed rates of permanent surgical morbidity and mortality of 1.9% and 2.7%, respectively, with an obliteration rate of 100%. [46]We presented a cohort comprising 445 patients treated with microsurgical resections in a large single center, and illustrated a permanent postoperative morbidity of 14.8% and a mortality of 7.9%. Even minor changes such as hydrocephalus or a small visual field deficit were assessed and rated as a deficit.…”
Section: Discussionmentioning
confidence: 99%
“…[45] Theofanis et al reported 264 patients treated with microsurgery and showed rates of permanent surgical morbidity and mortality of 1.9% and 2.7%, respectively, with an obliteration rate of 100%. [46]We presented a cohort comprising 445 patients treated with microsurgical resections in a large single center, and illustrated a permanent postoperative morbidity of 14.8% and a mortality of 7.9%. Even minor changes such as hydrocephalus or a small visual field deficit were assessed and rated as a deficit.…”
Section: Discussionmentioning
confidence: 99%
“…3,26 On the contrary, 2 studies found increased complication rates after preembolization. 15,28 In the 1990s and early 2000s, embolization series usually showed a comparable rate of new deficits (0%-22%) and even certain mortality (0%-4.3%). 19,29 A recent review of approximately 1300 mostly low-grade AVMs found a mortality rate of 1.6%, morbidity rate of 6.2%, and an occlusion rate of 29%.…”
Section: Use Of Embolization and Radiosurgerymentioning
confidence: 99%
“…Microsurgical resection, in select cases, can offer durable and high cure rates with immediate elimination of future hemorrhage risk (5,34,40). Preoperative endovascular embolization using particle or liquid embolic materials may potentially make surgical excision of these AVMs less daunting by reducing operative time and decreasing blood loss (10,41).…”
Section: Discussionmentioning
confidence: 99%
“…Microsurgery continues to play a role, albeit controversial, in the treatment of AVMs despite remarkable advances in radiosurgery and endovascular techniques (5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%